Does Systems Differentiation Present a Risk for Contemporary Society? - Šubrt, Jiří (Teorie vědy / Theory of Science, 2009)
For Niklas Luhmann modern society is a functionally differentiated society, i. e. it is composed of heterogeneous but equal parts which are relatively independent and are defined as social sub¬systems. Luhmann’s analysis presents contemporary society as a whole differentiated into functionally dependent yet autonomous sub-systems that constitute neighbouring worlds for each other. This raises the question of the existence or non-existence of potential unifying forces or integration mechanisms. In Luhmann’s view the main problem is the non-existence of means of “metacommunication”. The development of specialised media and codes in the individual sub-systems increases the overall complexity of the social system, but does not entail the metacom¬munication that would make possible the self-observation and self-reference of the social system as a whole.